Shunt loudspeaker using nonlinear energy sink. (15th September 2019) - Bitar, D.; Gourdon, E.; Lamarque, C.-H.; Collet, M.
Abstract: The present paper aims to apply the concept of energy pumping for noise reduction at propagation and reception paths. This phenomenon consists in irreversible energy transfer from a linear primary system to a nonlinear energy sink, where the energy is finally dissipated. In this study, we turn a loudspeaker to an electroacoustic absorber by connecting at its transducers terminals a passive nonlinear shunt circuit playing the role of an absorber. The equivalent model consists of a linear structure describing the displacement of the loudspeaker, linearly coupled to a cubic nonlinear energy sink. For the case of 1:1 resonance, the Invariant manifold approach is applied for different time scales. It enables the detection of the slow invariant manifold and equilibrium and fold singularities at the fast and slow time scales respectively. This methodology provides a predictive tool allowing the design of the nonlinear energy sink for better control of the main system. The analytical and numerical results show that the nonlinear shunt circuit managed to expand the frequency band of the controlled system.